Awareness and Adoption Rates of Menstrual Cups Among Adolescents and Young Women - Priyadarshini, Pratikshya; M. Kaavya, M. Kaavya (Journal of Neonatal Surgery, 2025)
Menstrual hygiene management is a crucial aspect of women's reproductive health. Menstrual cups have emerged as a sustainable, cost-effective alternative to conventional menstrual products like sanitary pads and tampons. However, the awareness and adoption rates of menstrual cups remain limited, particularly among adolescents and young women.To assess the awareness levels, adoption rates, and factors influencing the use of menstrual cups among adolescents and young women aged 15-30 years.A study was conducted involving 300 participants from educational institutions and community health centers. A structured questionnaire and semi-structured interviews were used to collect data on awareness, usage patterns, and barriers to adoption. Quantitative data was analyzed using SPSS software, while qualitative data was analyzed thematically.Out of 300 participants, 72% were aware of menstrual cups, while only 25% had used them. Among users, 80% reported satisfaction due to comfort, cost-effectiveness, and reduced menstrual cramps. However, fear of discomfort, lack of knowledge about insertion and removal, and cultural misconceptions were identified as primary barriers to adoption.Although menstrual cups offer significant advantages, their acceptance among young women is hindered by misinformation and social stigma. Targeted awareness campaigns and educational programs can help improve acceptance and accessibility.